2007
DOI: 10.1152/ajpendo.00584.2006
|View full text |Cite
|
Sign up to set email alerts
|

R-(+)-α-lipoic acid inhibits endothelial cell apoptosis and proliferation: involvement of Akt and retinoblastoma protein/E2F-1

Abstract: Lipoic acid was recently demonstrated to improve endothelial dysfunction or retinopathy not only in rats but also in diabetic patients. We tested the hypothesis that R-(+)-α-lipoic acid (LA) directly affects human endothelial cell (EC) function (e.g., apoptosis, proliferation, and protein expression), independent of the cells' vascular origin. Macrovascular EC (macEC), isolated from umbilical (HUVEC) and adult saphenous veins and from aortae, as well as microvascular EC (micEC) from retinae, skin, and uterus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…This antiapoptot- ic action of ALA might be mediated through activation of AMP-activated protein kinase or acutely transforming retrovirus AKT8 in rodent T cell lymphoma (AKT), as suggested in previous studies. 24,27 Further studies are necessary to elucidate the molecular mechanism of antiapoptotic action of ALA in HAECs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This antiapoptot- ic action of ALA might be mediated through activation of AMP-activated protein kinase or acutely transforming retrovirus AKT8 in rodent T cell lymphoma (AKT), as suggested in previous studies. 24,27 Further studies are necessary to elucidate the molecular mechanism of antiapoptotic action of ALA in HAECs.…”
Section: Discussionmentioning
confidence: 99%
“…3,[7][8][9] Based on previous studies 24,27 showing protective effects of ALA on endothelial cells, we examined the effect of ALA on reendothelialization by immunohistochemical staining for CD31, an endothelial-specific marker, on the sections of arteries harvested at various points (3, 10, and 14 days after injury). ALA significantly increased CD31 reactivity on the luminal surface of arteries at 10 to 14 days after injury, whereas a CD31 signal was undetectable in injured arteries without ALA administration ( Figure 6A).…”
Section: Ala Accelerates Reendothelialization After Bi and Inhibits Pmentioning
confidence: 99%
See 1 more Smart Citation
“…LA induces Akt phosphorylation in human umbilical vascular endothelial cells (32) and the THP-1 human monocyte cell line (33). Using isolated rat hepatocytes, Diesel et al (34) also showed LA-induced PI3K activation, but suggested a mechanism different than as a thiol redox modulator.…”
Section: Insulin/ir/aktmentioning
confidence: 99%
“…Although several studies shows the anti-proliferative capacity of LA on tumor cells [28] [29] [30], on the other hand, one recent study have reported the beneficial effect of LA promoting cell survival, angiogenesis and neuroregeneration after brain injury [31]. In our study, LA increased the number of cells after 8 days in culture suggesting the applicability of using LA in cell culture to quicken proliferation ( Figure 6).…”
Section: Discussionmentioning
confidence: 42%